The Sensory Machinery of the Head Louse Pediculus humanus capitis: From the Antennae to the Brain - Ortega Insaurralde, Isabel; Minoli, Sebastián; Toloza, Ariel Ceferino; Picollo, María Inés; Barrozo, Romina B. (Frontiers in Physiology, 2019)
Insect antennae are sophisticated sensory organs, usually coated with sensory structures responsible for the detection of relevant signals of different modalities coming from the environment. Despite the relevance of the head louse Pediculus humanus capitis as a human parasite, the role of its antennal sensory system in the highly dependent relation established with their hosts has been barely studied. In this work we present a functional description of the antennae of these hematophagous insects by applying different approaches, including scanning electron microscopy (SEM), anterograde antennal fluorescent backfills and behavioral experiments with intact or differentially antennectomized lice. Results were analyzed together as a first approach to identify, describe and determine the modality and role of the different sensilla of the head louse antenna. SEM images allowed us to identify a total of 35 - 40 sensilla belonging to 7 different types, that according to their morphology and architecture are candidates to bear mechano-, thermo-, hygro- or chemo-receptor functions. The anterograde backfills revealed a direct neural pathway to the antennal lobes, which present 8 - 10 glomerular-like diffuse structures. In the 2-choice behavioral experiments, intact lice chose scalp odors, warm surfaces (i.e., 32 ºC) and avoided wet substrates. Ablation of the different flagellomeres of their antenna resulted in the loss of the behavioral responses, allowing us to discuss about the location and function of the different identified sensilla. This is the first study that integrates morphological and behavioral aspects of the sensory machinery of head lice involved in host perception.